Becoming an ESL Researcher: A Personal Monologue - Irfan Ahmed Rind (National Research University Higher School of Economics, 2021)
This reflective paper narrates my research journey from a naïve researcher to a critic and from a behaviorist to a post-structuralist. It highlights the different philosophical, methodological, and theoretical dilemmas I faced in conceptualizing students' experiences in an English as a Second Language program in higher education during my doctoral studies. This journey is divided into three phases: construction, deconstruction, and reconstruction. In the construction phase, I conceptualized students' experiences from my own established knowledge, which was grounded in my presumptions about teaching and learning. During the deconstruction phase, I questioned my understanding of knowledge and social realities. In the reconstruction phase, I interacted with Phenomenography, Activity Theory, Symbolic Interactionism, Communities of Practice, and Bourdieusian Structuralism. This paper narrates these interactions, focusing mainly on the dilemmas I faced as a researcher. These reflections could be highly beneficial for new researchers who may face the same situations at different stages of their research careers.